The Influence of Product Quality and e-WOM on iPhone Smartphone Purchasing Decisions Generation Z in Surabaya: e-WOM, Product Quality, Purchasing Decisions - Tias Andarini Indarwati; Ahmad Fauzani Sabilal Arif (International Journal of Social, Economic, and Business, 2025)
The iPhone has emerged as a symbol of modern identity and social prestige among Generation Z consumers in Surabaya. This study aims to examine the extent to which product quality and electronic word of mouth (e-WOM) influence the purchasing decisions of this consumer group. Employing a quantitative research design, the study utilized purposive sampling to select respondents aged between 18 and 26 who are current iPhone users. Data were gathered through structured online questionnaires and analyzed using multiple linear regression through SPSS software. The results indicate that both product quality and eWOM exert a significant and positive influence on purchasing decisions, both individually and jointly. Product quality reflected in features such as design aesthetics, performance, durability, and overall reliability was identified as a key determinant in consumer decisionmaking processes. Concurrently, e-WOM, particularly through social media platforms, online reviews, and influencer recommendations, was found to play a pivotal role in shaping perceptions, building trust, and enhancing the likelihood of purchase. These results highlight the dual importance of maintaining superior product standards and strategically engaging with digital communication channels. For practitioners, the study suggests prioritizing quality enhancement while simultaneously investing in digital marketing strategies that resonate with the online habits and preferences of Generation Z. Encouraging positive consumer feedback and optimizing brand visibility across digital platforms may further strengthen purchasing motivation. Future research is recommended to incorporate additional variables such as brand image, lifestyle orientation, or perceived value to develop a more comprehensive model of consumer behavior in the premium smartphone segment.